2002
DOI: 10.1007/s00213-002-1030-5
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous cocaine and heroin self-administration in rats selectively bred for differential saccharin intake: phenotype and sex differences

Abstract: Female rats selectively bred for higher saccharin intake show more rapid and successful acquisition of IV self-administration of a low dose of cocaine than those bred for low saccharin intake. Female rats (compared with males) consistently showed accelerated rates of acquisition and maintenance (PR) of cocaine self-administration and acquisition of heroin self-administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
208
13

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(240 citation statements)
references
References 82 publications
(103 reference statements)
18
208
13
Order By: Relevance
“…Lower unit doses might have revealed more subtle differences with respect to acquisition (Carroll et al, 2002). Motor activation in response to novel stressors and experimentally elevated levels of transcription factors in the striatum correlate well with rapid acquisition of 'low dose' cocaine self-administration behavior (Piazza et al, 2000;Mantsch et al, 2001;Colby et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Lower unit doses might have revealed more subtle differences with respect to acquisition (Carroll et al, 2002). Motor activation in response to novel stressors and experimentally elevated levels of transcription factors in the striatum correlate well with rapid acquisition of 'low dose' cocaine self-administration behavior (Piazza et al, 2000;Mantsch et al, 2001;Colby et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Female rats show greater behavioral sensitization after repeated cocaine injections than do male rats (Glick et al, 1984;van Haaren et al, 1991;Chin et al, 2002;Hu et al, 2003). They also acquire cocaine self-administration more readily than male rats (Lynch et al, 1999;Lynch et al, 2001;Carroll et al, 2002;Hu et al, 2004).…”
mentioning
confidence: 92%
“…Estradiol (E) is thought to modulate the reinforcing effects of cocaine (Roberts et al, 1989;Grimm et al, 1997;Lynch et al, 2000;Lynch et al, 2001;Carroll et al, 2002;Hu et al, 2004;Jackson et al, 2006). For example, female rats will work harder for cocaine during estrus than during other phases of the estrous cycle (Roberts et al, 1989;Carroll et al, 2002) and E treatment given to ovariectomized (OVX) rats enhances the motivation to self-administer cocaine (Becker et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory and others have shown that indirect dopamine agonists like cocaine induce greater behavioral (Bowman and Kuhn, 1996;Walker et al, 2001a) and neuroendocrine (Walker et al, 2001b) effects in female than male rats. Female rats trained to self-administer cocaine on a progressive ratio schedule have higher break points than males (Roberts et al, 1987;Carroll et al, 2002), and acquisition, maintenance and reinstatement of cocaine self-administration are greater in female rats Carroll, 1999, 2000;Hu et al, 2004). However, Caine et al (2004) using a relatively hightraining dose of cocaine found that male rats acquired self-administration earlier than females.…”
Section: Introductionmentioning
confidence: 98%